Filter Sea Core-Dynamic Light-Coupled High-Efficiency Solar Desalination Device - Lu, Tingyu; Shuai, Kang (International Journal of Natural Resources and Environmental Studies, 2025)
This template explains and demonstrates how to prepare your camera-ready paper for Warwick Evans Publishing. The best is to read these instructions and follow the outline of this text. Please make the page settings of your word processor to A4 format (21 x 29.7 cm); with the margins: bottom 1.9 cm (0.74 in) and top 2.5 cm (0.98 in), right/left margins must be 2 cm (0.78 in). All manuscripts must be in English, also the table and figure texts, otherwise, we cannot publish your paper. All manuscripts must be in English, also the table and figure texts, otherwise, we cannot publish your paper.